ACUPRESSURE THERAPY LOWERS BLOOD PRESSURE IN ELDERLY WITH HYPERTENSION AT TRESNA WERDHA JAKARTA - Maryati Maryati; Laras Adythia Pertiwi (Avicenna: Jurnal Ilmiah, 2022)
Background: Acupressure is a treatment that uses finger compression techniques on acupuncture points instead of needle sticks in the acupuncture system. This treatment is safe because it is non-invasive and contains specific substances that apply acupressure to acupuncture points. Accelerates the flow of life energy throughout the body. The aim of this study was to determine the effect of acupressure therapy on lowering blood pressure in older people with hypertension according to the Tresna Werdha Method. The design used is quasi-experimental using a non-randomized pre-test and post-test control group approach. The population of this study was elderly and using a targeted sampling technique, a sample of 18 of hers was included, consisting of 9 of hers in the intervention and control groups. result: Results showed that acupressure therapy had a significant effect on lowering systolic blood pressure (p-value = 0.001 < 0.05) and diastolic blood pressure (p-value = 0.04 < 0.05). Conclusion: Based on the results of this study, acupressure therapy has been shown to lower blood pressure in older adults with hypertension and may be used as an alternative, non-pharmacological treatment in the treatment of hypertension.